2016
DOI: 10.1016/j.puhe.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

The perceived effects of singing on the health and well-being of wives and partners of members of the British Armed Forces: a cross-sectional survey

Abstract: Objectives A survey to explore the extent to which a choir programme associated with the British Armed Forces provides benefits of wives and partners and families of military personnel. Study design A cross-sectional survey. Method Online self-completion questionnaires to survey 464 choir members and 173 committee members who were also participants in the choirs. Results Large majorities of participants report personal and social benefits from their engagement in choirs, as well as benefits for their health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…A novel questionnaire was developed and distributed by the first author, guided by the work of Clift and Hancox 19 and Clift et al 20 This survey was piloted with 10 choristers, qualitative feedback was assimilated by the researcher and revisions were made. The final questionnaire comprised of 28 statements that were categorised under four headings of physical, social, emotional and spiritual (see Supplementary Appendix B for breakdown).…”
Section: Benefits Of Singing In a Choir Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…A novel questionnaire was developed and distributed by the first author, guided by the work of Clift and Hancox 19 and Clift et al 20 This survey was piloted with 10 choristers, qualitative feedback was assimilated by the researcher and revisions were made. The final questionnaire comprised of 28 statements that were categorised under four headings of physical, social, emotional and spiritual (see Supplementary Appendix B for breakdown).…”
Section: Benefits Of Singing In a Choir Questionnairementioning
confidence: 99%
“…9,10,22,32,33 Perceptions of singers themselves have been explored in a few studies, most notably an international study of 1,000 choristers and their perceptions of psychological wellbeing. 20,19,34 The largest study identified to date is by Clift et al who administered a large-scale, cross-national survey to assess choral singers' perceptions of the effects of singing in Australia, Germany and england. This sample consisted of 591 choral singers with an average age of 61 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was formed in January 2013 by the hospice’s music therapist whose vision was to create a choir modeled on Gareth Malone’s work with the military wives’ choirs where “music and singing will help the women through a difficult time of worry and separation” (The Choir: Military Wives, (2018)). As Clift et al (2016; 93) have noted, “long and unpredictable duty hours together with periodic redeployments and the risk of injury or death, can have an impact on the psychological and physical wellbeing of family members” of those serving in the military. A parallel may be seen between the military wives’ feelings of an uncertain future, isolation, vulnerability, and reluctance to enjoy themselves while their husbands were on a tour of duty, and similar feelings, though for different reasons, felt by the families of children being cared for at the hospice.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, government health reports refer to the need to build flourishing communities where individuals can feel a sense of belonging as an essential component of health (South, 2015). Qualitative and quantitative studies have demonstrated that being engaged in music activities, particularly singing in groups, can improve quality of life (Bailey and Davidson, 2003; Clift et al, 2008, 2010, 2016; Livesey et al, 2012; Tonneijck, Kinébanian and Josephsson, 2008)…”
Section: Introductionmentioning
confidence: 99%